Intermediate algebra: - Bello, Ignacio (McGraw-Hill, 2006)
Intermediate Algebra prepares students for further courses in the college math curriculum. Students of all backgrounds will be delighted to find a refreshing book that appeals to every learning style and reaches out to diverse demographics. Through down-to-earth explanations, patient skill-building, and exceptionally interesting and realistic applications, this worktext will empower students to learn and master algebra in the real world.